Paving the Way to Understand Autoantibody-Mediated Epilepsy on the Molecular Level - Seebohm, Guiscard; Piccini, Ilaria; Strutz-Seebohm, Nathalie (Frontiers in Neurology, 2015)
Correct function of neuronal networks is enabled by a delicate interplay among neurons communicating with each other. One of the keys is the communication at chemical synapses where neurotransmitters like glutamate, GABA, and glycine enable signal transfer over the synaptic cleft. Thereby, the neurotransmitters are released from the presynapse and bind as ligands to specific receptors at the postsynaptic side to allow for modulation of the postsynaptic membrane potentials. The postsynaptic electrical signal, which is highly modulated by voltage-gated ion channels, spreads over the dendritic tree and is thus integrated to allow for generation of action potentials at the axon hillock. This concert of receptors and voltage-gated ion channels depends on correct function of all its components. Misfunction of receptors and/or voltage-gated potassium channels (VGKC) leads to diverse adverse effects in patients. Such malfunctions can be the result of inherited genetic alterations or pharmacological side effects by drugs. Recently, autoantibodies targeting receptor or channel complexes like NMDAR, AMPAR, GABA-receptors, glycine receptors, LGI1 or CASPR2 (previously termed as VGKC-complex antibodies) have been discovered. The presence of specific autoantibodies against these targets associates with severe forms of antibody-mediated encephalitis. Understanding the molecular details of autoantibody actions on receptor and VGKC complexes is highly desirable and may open the path to develop specific therapies to treat humoral autoimmune encephalitis. Here, we summarize the current knowledge and discuss technical approaches to fill the gap of knowledge. These techniques include electrophysiology, biochemical approaches for epitope mapping, and in silico modeling to simulate molecular interactions between autoantibody and its molecular target.